Equity, Growth, and Community: What the Nation Can Learn from America's Metro Areas - Chris Benner; Manuel Pastor (University of California Press, 2015)
In the last several years, much has been written about growing economic challenges, increasing income inequality, and political polarization in the United States. Addressing these new realities in America's metropolitan regions, this book argues that a few lessons are emerging: first, inequity is bad for economic growth; second, bringing together the concerns of equity and growth requires concerted local action; and third, the fundamental building block for doing this is the creation of diverse and dynamic epistemic (or knowledge) communities, which help to overcome political polarization and to address the challenges of economic restructuring and social divides.
Keywords: 330; Urban development; Economic development; Income distribution; Regional planning; Economic policy; Cities and towns - United States; Ballungsraum; Nachhaltige Stadtentwicklung; Regionales Wachstum; Regionalplanung; Kommunalpolitik; Bürgerbeteiligung; Share Economy; Wissensgesellschaft; USA